Hypoxio: a simple solution to preventing pericellular hypoxia in cell monolayers growing at physiological oxygen levels - Bagshaw, Olivia R. M. (Cytotechnology, 2019)
Culturing cells as adherent monolayers is a common approach in cell biology. For cell culture experiments to yield reliable results it is important to replicate in vivo conditions as faithfully as possible. Increasingly, researchers appreciate the importance of oxygen in cell physiology and the corresponding need to maintain physiologically relevant oxygen levels during experiments. However, although oxygen levels are sometimes monitored over the course of an experiment, this is virtually always in the incubator gas phase and not in the media bathing cells. When incubator oxygen levels are set to a physiologically appropriate level, typically 2–6%, the pericellular oxygen levels experienced by cells may be substantially lower, particularly under conditions where cells are respiring rapidly. We have developed a simple approach to prevent this problem. ‘Hypoxio’ is a software application that uses real time measurements of pericellular oxygen to coordinate media mixing via a tilt table. Hypoxio allows the user to set a threshold below which it initiates a mixing cycle of user-adjustable duration to abolish standing gradients associated with pericellular hypoxia. Here we describe Hypoxio, demonstrate its efficacy, and direct the reader to our GitHub site for downloadabale software and a description of hardware.